NEW RECORD OF THE GRUB FISH, PARAPERCIS ALBOGUTTA (GUNTHER) FROM BOMBAY WATERS - Pillai, S Krishna; Somvanshi, V S (Indian Journal of Fisheries, 2011)
A Grub fish, Parapeicis albogutta (Gunther) has been recorded fromBombay waters for the first time. Various morphometric and meristic counts havebeen described